Performance of Lentil as Affected by Reduced Tillage and Mechanical Seeding (SAARC Journal of Agriculture, 2020)
Generally, lentil seeds are sown following the traditional farming practice with 3-4 numbers of ploughing combined with broadcasting method in lentil growing countries. This is time consuming and costly. The objective of this study was to evaluate the lentil performance as affected by different mechanical seeding system as well as seeding device. There were seven different treatments of which two tillage systems like i) broadcasting after4 times tillage (CT) and ii) broadcasting after tillage with two wheeler driven High Speed Rotary Tiller (HSRT), and five direct mechanical seeding systems like TT+BP =one tillage + bed planting seeding (BP+Pl), TBP =Direct bed planting seeding (BP), TPTOS =Two wheeler operated Seeder (PTOS), TST = Strip tillage seeding (ST) and TZ =Zero tillage seeding (Z). The experiment was carried out by a randomized complete block design (RCBD) with three replications. From the results it was revealed that yield was increased from0.56 % to 10.42% in mechanical seeding system than CT. The findings also demonstrated that BP increased yield of about 10.42% with 49.31% of lower fuel consumption which saved 48.1% time compared to CT. The HSRT gave numerically higher yield compare to ST than CT but lower than BP, BP+Pl and PTOS. Zero tillage seeding system gave the minimum seed yield compare to others which was 9.67% and 19% lower than that of CT and BP, respectively. In mechanical seeding systems, bed planting exhibited higher root volume and density compare to that of others, but lower to CT and HSRT.SAARC J. Agri., 18(1): 51-60 (2020)